Heart-design nexus: the emotion algorithm - Mohd Lokman, Anitawati (Penerbit UiTM (UiTM Press), 2025)
The journey that led to this book began nearly 30 years ago when, as a young doctoral student, I first encountered the concept of Kansei Engineering. What started as an academic exploration soon became a lifelong passion, a quest to understand how human emotions shape our interactions with the designed world, and how those insights can be systematically applied to create more meaningful products, spaces, and experiences. Throughout my career, I have been privileged to witness the evolution of Kansei Engineering, from a specialised Japanese methodology to a globally recognised approach that spans disciplines and cultures. The opportunity to learn directly from Professor Mitsuo Nagamachi, the pioneer of Kansei Engineering, profoundly shaped my understanding of the field and inspired me to contribute my own methodological innovations. This book, "Heart-Design Nexus: The Emotion Algorithm", represents both a culmination and a continuation of that journey. It is at once a reflection on the historical development of Kansei Engineering, a documentation of my personal contributions to the field, and a forward-looking exploration of emerging trends and future possibilities. In writing this book, I have attempted to balance theoretical rigour with practical application and academic precision with accessible language. My aim is to speak to multiple audiences, from design practitioners seeking methodological guidance to researchers exploring theoretical frameworks, and from students beginning their Kansei joumey to experienced professionals looking to deepen their understanding of emotion-driven design. The title "Heart-Design Nexus" was chosen deliberately to capture the essence of what makes Kansei Engineering so powerful: its ability to bridge the seemingly unbridgeable gap between the subjective realm of human emotion and the objective world of design specifications. The subtitle, "The Emotion Algorithm", reflects the systematic, methodical approach that transforms fleeting feelings into tangible design parameters. It is my sincere hope that "Heart-Design Nexus" will contribute to the continued growth and application of Kansei Engineering, inspiring a new generation of designers, engineers, and researchers to embrace the emotional dimensions of their work. In a world increasingly mediated by technology, understanding how to create products and experiences that resonate emotionally has never been more important. As you journey through these pages, I invite you to consider not only the methodologies and case studies presented but also the broader implications of emotion-driven design for our collective future. How might these approaches help create a world that is not just functionally efficient but emotionally enriching? How might they contribute to more meaningful connections between people and the designed environments that surround them? The exploration of the Heart-Design Nexus is an ongoing journey, one that I am honoured to share with you through this book.